AICCRA validation report: Piloting and validating the Climate Security Sensitivity Scoring Tool (CSST): Evidence from the field on the climate security sensitivity of the climate smart village approach in Cinzana, Mali. - Sarzana, Carolina; Samake, Oumar B; Jaquet, Stéphanie (2023)
A one-day workshop in Ségou, Mali was organized to test the results of the Climate Security Sensitivity Tool (CSST) and reflect on the reliability of its recommendations. This document reports on the results of the CSST piloted on the Climate Smart Village (CSV) approach implemented in Cinzana and on the outcomes of the workshop that reflected upon these results and recommendations. The workshop validated most drivers of conflict and insecurity flagged by the CSST, while pointing out that the human hazards risk indicator was overestimated since most conflict experienced are resource-related rather than linked to the threats of armed groups as well as the fact that the vulnerable groups indicator does not fully capture the complexity of marginalized groups in the region. The workshop highlighted the program's achievements, including advancements in agricultural technologies, gender empowerment through market gardening, and improved community collaboration. However, shortcomings in addressing institutional natural resource management and awareness-raising initiatives were noted. Participants emphasized the repercussions, such as deforestation and resource conflicts, signaling the need to prioritize institution-building and education in CSV programs. Aligning with CSST recommendations, the findings underscore the significance of integrating peace-focused elements to bolster climate adaptation strategies and prevent resource-related conflicts in vulnerable contexts. The workshop's outcomes validated the CSST's utility and demonstrated that the tool can provide suitable recommendations, especially when coupled with localized insights, enhancing its value in crafting context-specific climate adaptation programs that effectively address the drivers of conflict and insecurity in vulnerable regions.